2015
DOI: 10.1038/npp.2015.282
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled Trial of Methylphenidate or Galantamine for Persistent Emotional and Cognitive Symptoms Associated with PTSD and/or Traumatic Brain Injury

Abstract: We report findings from a 12-week randomized double-blinded placebo-controlled trial of methylphenidate or galantamine to treat emotional and cognitive complaints in individuals (n = 32) with a history of PTSD, TBI, or both conditions. In this small pilot study, methylphenidate treatment was associated with clinically meaningful and statistically significant improvement compared with placebo on the primary outcome, a measure of cognitive complaints (Ruff Neurobehavioral Inventory-Postmorbid Cognitive Scale), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 41 publications
7
71
0
Order By: Relevance
“…MPH may have the potential to correct this deficit by accelerating the adaptation of error-driven learning to environmental volatility. Supporting this, a recent multicenter randomized controlled trial found that treatment with MPH was associated with a remarkably robust reduction in symptoms of posttraumatic stress disorder (PTSD) (McAllister et al 2015). Future research can incorporate functional neuroimaging along with the computational approach described here in order to assess the influence of MPH on the dACC-LC circuit both in normal individuals and individuals with anxiety disorders.…”
Section: Discussionmentioning
confidence: 98%
“…MPH may have the potential to correct this deficit by accelerating the adaptation of error-driven learning to environmental volatility. Supporting this, a recent multicenter randomized controlled trial found that treatment with MPH was associated with a remarkably robust reduction in symptoms of posttraumatic stress disorder (PTSD) (McAllister et al 2015). Future research can incorporate functional neuroimaging along with the computational approach described here in order to assess the influence of MPH on the dACC-LC circuit both in normal individuals and individuals with anxiety disorders.…”
Section: Discussionmentioning
confidence: 98%
“…[39][40][41] Therapeutically, GAL is associated with improved episodic memory and amelioration of depressive symptoms in TBI patients. 42 GAL has also been shown to improve cognitive function in patients with Alzheimer's disease and mild cognitive impairment. [43][44][45][46][47][48] Moreover, a substantial proportion of patients who failed to recover with donepezil exhibited benefits when switched to GAL, suggesting that previous failures in responding to certain AChEIs do not predict responses to others, such as GAL.…”
Section: Introductionmentioning
confidence: 99%
“…As has been noted in related literature, despite the need for interventional studies to address cognitive problems after TBI, recruitment for this and similar studies is extremely challenging (McAllister et al, 2015). The initial target for this study was to recruit 50 patients into each treatment group, for a total of 200 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that MPH improves performance on measures of attention, memory, verbal fluency, processing speed, motor performance, and arousal, and is also associated with improvements in subjective (self or informant) assessment of cognitive functioning (Gualtieri and Evans, 1988;Johansson et al, 2015;Kaelin et al, 1996;McAllister et al, 2015;Plenger et al, 1996;Whyte et al, 1997;Whyte et al, 2004;Whyte et al, 2002;Willmott and Ponsford, 2009). Indeed, the Defense and Veterans Brain Injury Center's Neurobehavioral Guidelines Working Group evidence-based review of pharmacotherapies for post-traumatic cognitive impairments recommended MPH at the Guideline level for attention and processing speed impairments, and at the Option level for general cognitive deficits and memory impairments (Warden et al, 2006).…”
Section: Introductionmentioning
confidence: 99%